The Effect of Hedonic and Utilitarian Values on the Purchase Intention of Skins in Mobile Legends: A Case Study of Players in Kupang City - Jehuda Sir; Yanti S. Giri (Journal of Practical Management Studies, 2026)
The monetization of cosmetic virtual goods has reshaped digital gaming economies, raising questions about the evaluative mechanisms underlying non-functional purchases. This study examines the relative influence of hedonic and utilitarian values on the purchase intention of skins in Mobile Legends among players in Kupang City, Indonesia. Grounded in dual-value consumption theory and the theory of planned behavior, the research employs a quantitative explanatory design using multiple linear regression analysis on survey data from active players. The findings reveal that both hedonic and utilitarian values significantly influence purchase intention; however, utilitarian value demonstrates a stronger effect. This result challenges the assumption that cosmetic digital consumption is predominantly hedonic and suggests that rational cost-benefit evaluation plays a decisive role, particularly in non-metropolitan contexts. The study contributes to digital consumer behavior literature by highlighting the contextual hybridity of symbolic and economic value in virtual goods markets.